A Database of Experimentally Derived and Estimated Octanol–Air Partition Ratios (KOA) - Baskaran, Sivani; Lei, Ying Duan; Wania, Frank (Journal of physical and chemical reference data, 2021)
Equilibrium partition coefficients or partition ratios are a fundamental concept in physical chemistry, with wide applications in environmental chemistry. While comprehensive data compilations for the octanol–water partition ratio and the Henry’s law constant have existed for many years, no comparable effort for the octanol–air partition ratio (KOA) exists. Considering the increasing use of KOA in understanding a chemical’s partitioning between a wide variety of organic phases (organic phases in atmospheric particles, plant foliage, polymeric sorbents, soil organic matter, animal tissues, etc.) and the gas phase, we have compiled all KOA values reported in the published literature. The dataset includes more than 2500 experimentally derived values and more than 10 000 estimated values for KOA, in total covering over 1500 distinct molecules. The range of measured log10 KOA values extends from −2 to 13. Many more measured values have been reported in the log10 KOA range from 2 to 5 and from 6 to 11 compared to the range from 5 to 6, which is due to the complementary applicability range of static and dynamic measurement techniques. The compilation also identifies measured data that are judged not reliable. KOA values for substances capable of undergoing strong hydrogen bonding derived from regressions with retention times on nonpolar gas chromatographic columns deviate strongly from values estimated by prediction techniques that account for such intermolecular interactions and should be considered suspect. It is hoped that the database will serve as a source for locating existing KOA data and for the calibration and evaluation of new KOA prediction techniques.